Clinical outcomes of adults with hemophagocytic lymphohistiocytosis treated with the HLH-04 protocol: a retrospective analysis. Issue 7 (6th June 2020) - Bubik, Rachel J.; Barth, Dylan M.; Hook, Christopher; Wolf, Robert C.; Muth, Jessica M.; Mara, Kristin; Patnaik, Mrinal S.; Pruthi, Rajiv K.; Marshall, Ariela L.; Litzow, Mark R.; Elliott, Michelle A.; Hogan, William J.; et al.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare syndrome of pathologic immune activation in children that is increasingly being recognized in adults. Efficacy data for the HLH-04 protocol in adults is lacking. This study retrospectively analyzed 31 adult patients, median age 46 years, who received HLH-04 from 1/1/2004 to 5/1/2018. HLH etiology included malignancy ( n  = 9), autoimmune ( n  = 8), infection ( n  = 8), and idiopathic ( n  = 6). Eighteen patients were evaluable for response at week 4 with 7 having no response, 11 reaching partial response, and 0 reaching complete response (CR). Six patients eventually achieved CR at a median 195 days. The 1-year overall survival (OS) was 35% and median OS was 3.2 months. Univariate analysis showed shorter survival for hemoglobin <9 g/dL (HR 4.29, p  = 0.003), platelets <100 × 10 9 /L (HR 4.06, p  = 0.027), ANC <1 × 10 9 /L (HR 5.24, p  = 0.001), and total bilirubin >1.2 mg/dL (HR 3.30, p  = 0.022). Outcomes of adults treated with HLH-04 remain dismal and newer treatment modalities are needed.